Efficacy and influencing factor analysis of high-intensity focused ultrasound therapy for abdominal wall endometriosis: a case series - Hui Cheng; Xiaogang Zhu; Yuyin He; Mengying Liu; Min Xue; Xin Sun (International Journal of Hyperthermia)
Objective The aim of this retrospective study was to investigate the short-term and long-term efficacy of high-intensity focused ultrasound (HIFU) therapy for abdominal wall endometriosis (AWE) and explore its potential influencing factors.Materials and methods A total of 80 patients with AWE who underwent HIFU therapy were retrospectively analyzed. Follow-ups were also conducted to evaluate the changes in lesion size and pain relief. Multivariate logistic regression analysis was applied to investigate factors influencing HIFU therapy for AWE.Results Among the 80 patients with AWE who received HIFU therapy, the effective rates were 76.3%, 80.5%, and 90.5% after 3, 12 and 24 months of follow-up, respectively. Multivariate logistic regression analysis revealed that the AWE lesion diameter and sonication intensity had statistically significant effects on the 3-month and 12-month efficacy of HIFU therapy for AWE, while age, BMI, disease duration, average sonication power and grey-scale changes did not have statistically significant effects. Four patients with AWE experienced recurrence after HIFU therapy, for a three-year cumulative recurrence rate of 6.3%. Furthermore, ten patients required reintervention after treatment, for a five-year cumulative reintervention rate of 13.9%.Conclusions This study further confirmed the safety and effectiveness of HIFU therapy for AWE. Factors such as AWE lesion diameter and sonication intensity have been identified as key influencers affecting the short-term and long-term efficacy of HIFU therapy for AWE. The first two years following HIFU therapy constitute crucial periods for observation, and judiciously extending follow-up intervals during this timeframe is advised.